Immunization Coverage of Covid-19 among Attendants Accompanying Patients in Gulab Devi Hospital-Pakistan - Muhammad Mansoor Ali, Muhammad Zubair, Muhammad Umer Abdullah, Muhammad Ahmad Javed, Muneeza Wazir, Fizza Javed, Muntha Chaudhari, Zahra Niaz (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Covid-19 is one of the major pandemics and health crisis in global history along with SARS-CoV & MERS-CoV. Aim: To find the frequency and distribution of coverage of Covid-19 vaccination among attendants accompanying the patients in Gulab Devi Hospital. Methodology: This cross sectional study used convenience sampling technique. The study population comprised of 386 respondents estimated via S size software. Our data collection team visited various wards & OPDs of hospitals & conducted interviews for the purpose. A structured questionnaire was filled for obtaining the data. Frequency and percentages were calculated for categorical variables while mean and standard deviation was calculated for numeric variable by using SPSS v-23. Results: The vaccination coverage of Covid-19 Immunization was as follows: 69% of our respondents were partially Vaccinated (1 or 2 doses), 14% fully vaccinated (3 or more doses) 17% were non vaccinated. Conclusions: Significant proportion of the participants were partially vaccinated or not vaccinated against COVID-19, indicating the need for further efforts to improve vaccination coverage thus findings emphasized the need for targeted educational campaigns. Keywords: COVID-19, Vaccination Coverage, Attendants, Effectiveness and Response Rate.